Underreported use of non-steroidal anti-inflammatory drugs in an outpatient gastroenterology practice: a prospective office-based survey - Raj Majithia; David A. Johnson; Michael J. Ryan; F. Taylor Wootton; Jeff Willis; Kelvin Hornbuckle; Whitney Brooks (Gastroenterology Insights, 2013)
Non-steroidal anti-inflammatory drugs (NSAIDs) are one of the most commonly used class of medications worldwide. It is estimated that more than 20 million people take NSAIDs daily. We examined the underreported use of NSAIDs on a standardized office intake assessment questionnaire of patient reported medications. A questionnaire was administered to patients following written and verbal confirmed report of current medications to nursing staff. One hundred consecutive patient intake assessments were evaluated from the patient intake sheets for a busy private gastroenterology specialty practice. After patients listed their current medications, they were given a survey and asked to acknowledge any use of 30 non-prescription formulations that contained NSAIDs. Patients filled these surveys while waiting for the health care provider who then reviewed the response accuracy with the patient during the visit. Changes in the patient‘s initial and subsequently corroborated use or non-use of NSAIDs were recorded and tabulated. The educational level of all participants was also assessed. Of the 100 surveys completed, 6% of patients had not completed high school, 19% had completed high school, 8% had started but not finished college, 54% had completed college, 2% had started but not finished graduate school, and 11% had completed graduate school. The educational level of the patients did not correlate with underreporting of NSAID usage. On the survey, 18% of patients noted use of an NSAID listed that had not been reported verbally to nursing staff; 8% of those patients reported daily use, 15% weekly use and 76% reported use within the last month. Patients were then asked in the questionnaire as to the reason for not reporting medication intake to nurse; 14% stated they were never asked about the specific medication, 22% did not think the medications were important enough to list, 34% bought the medication with prescriptions, and 30% noted their reason as their doctor did not prescribe the medication to them. Using a prospective questionnaire in a private practice gastrointestinal office, these data show that patients underreport use of non-prescription NSAIDs. Based on the data, it is clear that this underreporting can have a detrimental effect on procedure related as well as long-term patient care. Future studies would be needed to examine the incidence of side effects due to underreporting of NSAIDs.